Dose and strain dependent lethality of Usutu virus in an Ifnar−/− mouse model - Johanna M. Duyvestyn; Eleanor M. Marshall; Peter J. Bredenbeek; Barry Rockx; Martijn J. van Hemert; Marjolein Kikkert (npj Viruses)
Abstract Usutu virus (USUV) is a mosquito-borne zoonotic flavivirus with a geographic range that has expanded over recent years. Maintained in a transmission cycle between mosquito vectors and avian reservoirs the virus can cause large seasonal outbreaks in bird populations, but spillover into mammalian hosts has also been reported. While usually mild or asymptomatic in humans, neurological disorders are increasingly observed, which has boosted interest and the need for better understanding of the pathogenesis of various USUV lineages. In this study we inoculated interferon α/β receptor knockout (Ifnar−/−) mice with decreasing doses of USUV, monitoring symptoms and survival to determine a less lethal dose, and we directly compared isolates from three different viral lineages. We found that a Dutch isolate of USUV Africa-3 lineage is lethal at a dose of 20 pfu per mouse, which is considerably lower than what was anticipated based upon the literature. A Europe-2 strain showed an even higher virulence in this mouse model, compared to strains from Africa-3 and Europe-3 lineages—though this was not reflected in in vitro studies. These results enhance our understanding of the pathogenicity of different USUV strains and provide guidance for the use of low doses for inoculation in an Ifnar−/− animal model.